2020
DOI: 10.1111/jocn.15316
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mobility and pressure ulcer development in older adults: Excess movement and too little movement—Two sides of the one coin?

Abstract: Aim: To identify how activity and mobility lead to pressure ulcer development, using two objective assessments, one for mobility and one for early pressure ulcer detection.Methods: 150 older persons from long-term settings were followed up for 20 days, using an observational, quantitative, prospective study design. The study was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology statement. Visual skin assessment and sub-epidermal moisture assessments were unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(105 citation statements)
references
References 83 publications
1
103
1
Order By: Relevance
“…Moda Vitoriano Budri et al (2020). A relatively similar number of participants developed a VSA-PU or an SEM-PU regardless of whether they were high or low movers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moda Vitoriano Budri et al (2020). A relatively similar number of participants developed a VSA-PU or an SEM-PU regardless of whether they were high or low movers.…”
Section: Discussionmentioning
confidence: 90%
“…In the same study, of the 118 SEM‐PU observed, 51% ( n = 60) occurred among those classified as being low movers, and 49% ( n = 58) occurred among those classified as being high movers. It is somewhat surprising that an equal number of individuals (low and high movers) developed a VSA‐PU or an SEM‐PU (Moda Vitoriano Budri et al, 2020). The findings from the current study corroborate those of Moda Vitoriano Budri et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Dynamic conditions like repositioning and patient transfers may drag the skin over bony prominences, increasing both the friction and shearing forces. 18,19 This increases the risk of superficial tissue injury including skin tears and blister formation particularly in older adults given their skin atrophy, reduced collagen, and loss of elastin. 19 These movements may also make the skin tissue more vulnerable to deeper PIs.…”
Section: Friction and Shearmentioning
confidence: 99%
“…18,19 This increases the risk of superficial tissue injury including skin tears and blister formation particularly in older adults given their skin atrophy, reduced collagen, and loss of elastin. 19 These movements may also make the skin tissue more vulnerable to deeper PIs.…”
Section: Friction and Shearmentioning
confidence: 99%
“…A recent study 67 in the older population, also using this device among 150 participants cared for in long‐term settings, undertook SEM assessment and VSA to identify how activity and mobility lead to pressure ulceration. The authors, using an observational design, followed the participants up for 20 days and assessed mobility using a piezoelectric movement sensor and the activity subscale of the Braden scale.…”
Section: Early Tissue Damage Detectionmentioning
confidence: 99%